AFFECT OF ACTIVITY TRAVEL BEHAVIOR, AND TRANSIT ORIENTED DEVELOPMENT (TOD) ON SUBJECTIVE WELL BEING - CHE ISMAIL , CHE MOHAMAD AMIRUS SHAFUAN (Universiti Teknologi PETRONAS, 2018)

(untitled)
Activity travel behaviour is affecting subjective well-being. Thus, relationship between this is being study on this paper. Traveling mode is vary depending on motorized mode available for one to use it. Transit Oriented Development (TOD) is the model where it focus on transit availability in a land use. A development of a land or an area that maximize the land use to reduce the distance between one point to another and by providing a transport for the user to travel and to ease them to reach to another point. This help reducing the time travel needed and help one to undertake a series of event within the time constraint and capability constraint. To satisfy one’s need, they must be able to complete their daily task without having much difficulties. Having to travel to few place in single day is difficult for one especially if the travel distance is high and it takes longer time with less motorized mode available. Therefore, this study is to help one’s well-being to be achieved by being able to satisfy their need and interest within the constraint. A finding based on collected data will be provided to help in visualization the relationship between activity travel behaviour, TOD, and subjective well-being.